Maternal education and childhood immunization in Turkey - Mustafa Özer; Jan Fidrmuc; Mehmet Ali Eryurt (Global Labor Organization (GLO), 2017)
We study the causal effect of maternal education on childhood immunization rates. We use the Compulsory Education Law (CEL) of 1997, and the differentiation in its implementation across regions, as instruments for schooling of young mothers in Turkey. The CEL increased the compulsory years of schooling of those born after 1986 from 5 to 8 years. We find that education of mothers increases the probability of completing the full course of DPT and Hepatitis B vaccinations for their children. The results are robust to variation in regression specification and including various individual and community variables.
Keywords: H51; H52; I12; 330; DPT (diphtheria; pertussis and tetanus); Hepatitis B; Maternal Education; Vaccination; Difference-in-Difference-in-Difference; Instrumental variable